Ultrasound-guided Genicular Nerve Block in Comparison to Intra-articular Steroid Injection in Chronic Pain Due to Osteoarthritis Knee: A Double-blind Randomised Controlled Trial - Kalaivani Pushpakaran; Naveen Cherian Thomas; Judy Ann John; Madhavi Kandagaddala; S. Anitha; Lenny Vasanthan; Grace Rebekah; Shyamkumar Nidugala Keshava (Indian Journal of Physical Medicine & Rehabilitation)
Objective: The objective of this study was to assess the effectiveness of ultrasound (USG)-guided genicular nerve block (GNB) using bupivacaine in comparison to intra-articular corticosteroid (IACS) injection in reducing pain and improving function in persons with osteoarthritis (OA) knee. Design: This was a double-blind randomised controlled trial. Materials and Methods: This study was conducted at the outpatient clinics of the departments of physical medicine and rehabilitation and radiology in a tertiary care centre in South India. Participants (n = 50) with chronic pain due to OA knee were randomly assigned to two groups. Participants in the experimental group received USG-guided GNB using 0.5% bupivacaine and the control group received USG-guided IACS injection with 40 mg of Depo-Medrol + bupivacaine. Both the groups received exercises and education about joint protection measures. The primary outcome was assessed by mean change in knee pain by the Visual Analogue Scale (VAS) and improvement in functional ability using the Lequesne’s Functional Index (LFI) at 12 weeks of intervention. The secondary outcome was to identify any adverse events following the intervention. Results: Twenty-five patients were allotted in each of the treatment arms. Significant reduction in VAS and improvement in LFI at 4 and 12 weeks in both the experimental and control groups when compared to baseline (P < 0.05) were noted. The difference in mean change of VAS and LFI between the experimental and control groups was not statistically significant. There were no adverse events reported with either of the interventions. Conclusion: Both USG-guided GNB and IACS injections were effective and similar in reducing pain and improving function in persons with OA knee.